Expression of the AMPA Receptor Subunits GluR1 and GluR2 is Associated with Granule Cell Maturation in the Dentate Gyrus - Hagihara, Hideo; Ohira, Koji; Toyama, Keiko; Miyakawa, Tsuyoshi (Frontiers in Neuroscience, 2011)
The dentate gyrus produces new granule neurons throughout adulthood in mammals from rodents to humans. During granule cell maturation, defined markers are expressed in a highly regulated sequential process, which is necessary for directed neuronal differentiation. In the present study, we show that α-amino-3-hydroxy-5-methy-4-isoxazole propionate (AMPA) receptor subunits GluR1 and GluR2 are expressed in differentiated granule cells, but not in stem cells, in neonatal and adult dentate gyrus. Using markers for neural progenitors, immature and mature granule cells, we found that GluR1 and GluR2 were expressed mainly in mature cells and in some immature cells. A time-course analysis of 5-bromo-2'-deoxyuridine staining revealed that granule cells express GluR1 around 3 weeks after being generated. In mice heterozygous for the alpha-isoform of calcium/calmodulin-dependent protein kinase II, a putative animal model of schizophrenia and bipolar disorder in which dentate gyrus granule cells fail to mature normally, GluR1 and GluR2 immunoreactivities were substantially downregulated in the dentate gyrus granule cells. In the granule cells of mutant mice, the expression of both presynaptic and postsynaptic markers was decreased, suggesting that GluR1 and GluR2 are also associated with synaptic maturation. Moreover, GluR1 and GluR2 were also expressed in mature granule cells of the neonatal dentate gyrus. Taken together, these findings indicate that GluR1 and GluR2 expression closely correlates with the neuronal maturation state, and that GluR1 and GluR2 are useful markers for mature granule cells in the dentate gyrus.